SISTEM PENGONTROLAN TOTAL DISSOLVE SOLID (TDS) AIR PADA AKUARIUM IKAN HIAS AIR LAUT MENGGUNAKAN METODE FUZZY LOGIC MAMDANI - Muhammad Haichal Pambudi; Tri Nurwati; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Keeping ornamental fish means maintaining water quality and one way is to control the amount of dissolved solids or Total Dissolve Solid (TDS). In this research, the TDS parameters were controlled using the design of the TDS controller. In this research, the design process of the YL69 sensor was carried out as a sensor for reading the TDS value and setting the pump speed using a fuzzy logic controller. The research was conducted in a seawater aquarium as the medium. The results of this research, it can be seen that the tool is able to balance the TDS according to the setpoint membership function fuzzy, namely 35-50 ppt for 256 seconds and 189 seconds. The system can also return the response to the setpoint when disturbed with a recovery time of 67 seconds. The water discharge coming out of the pump can also be adjusted according to the difference between the aquarium TDS and the desired value. Keywords: TDS, fuzzy, membership function.